Contemporary Psychological Approaches to Life at the End of Life. Issue 1 (1st January 2014) - Carpenter, Brian D.
ABSTRACT When people have a serious life-limiting illness, physical symptoms are often prominent, both in the experience of the illness and in its treatment. No less important, however, are psychological symptoms. A holistic, bio-psycho-social-spiritual approach to quality of life near the end of life must address psychological distress of all types, including frank psychopathology, more moderate problems with living, and existential distress. Responding to mental health issues at the end of life requires (1) systematic and careful assessment, and (2) deployment of evidence-based treatments. In recent years, standardized assessment tools have been adapted or developed for use with people who have serious illness, and the same has happened with psychological treatments. Practitioners have several resources available to them. Given their practice orientation centered on meaningful engagement, occupational therapists can play an important role in responding to mental distress in patients with serious illness whose lives are becoming more circumscribed because of their medical condition or because of the mental distress itself. High-quality end-of-life care depends on scrupulous attention to the full spectrum of thoughts, feelings, and behaviors that unfold as death draws near.